Cellular senescence: all roads lead to mitochondria - Martini, Hélène; Passos, João F. (The FEBS journal, 2023)
Senescence is a multi‐functional cell fate, characterized by an irreversible cell‐cycle arrest and a pro‐inflammatory phenotype, commonly known as the senescence‐associated secretory phenotype (SASP). Emerging evidence indicates that accumulation of senescent cells in multiple tissues drives tissue dysfunction and several age‐related conditions. This has spurred the academic community and industry to identify new therapeutic interventions targeting this process. Mitochondrial dysfunction is an often‐unappreciated hallmark of cellular senescence which plays important roles not only in the senescence growth arrest but also in the development of the SASP and resistance to cell‐death. Here, we review the evidence that supports a role for mitochondria in the development of senescence and describe the underlying mechanisms. Finally, we propose that a detailed road map of mitochondrial biology in senescence will be crucial to guide the future development of senotherapies. Mitochondria play a central role in the development of cellular senescence. Senescence is characterized by several mitochondrial functional changes such as a decrease in OXPHOS, reduced levels of NAD+ and ATP, and accumulation of TCA cycle metabolites, DAMPs, and ROS. Here, we provide an overview of the recent findings demonstrating how these mitochondrial changes can contribute to the senescence‐associated growth arrest and the SASP.